2013
DOI: 10.3389/fneur.2013.00003
|View full text |Cite
|
Sign up to set email alerts
|

Refractory Intracranial Hypertension Due to Fentanyl Administration Following Closed Head Injury

Abstract: Background: Although the effects of opioids on intracranial pressure (ICP) have long been a subject of controversy, they are frequently administered to patients with severe head trauma. We present a patient with an uncommon paradoxical response to opioids.Case Report: A patient with refractory intracranial hypertension after closed head injury was managed with standard medical therapy with only transient decreases in the ICP. Only after discontinuation of opiates did the ICP become manageable without metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Once injected, morphine enters the blood stream, which carries it to the brain and other parts of the body where it acts primarily as an agonist of the μ opioid receptors in the central nervous system and in peripheral tissue. [58][59][60] Recently, Holbrook et al demonstrated that the administration of morphine for optimal control of pain and anxiety after injury may reduce the risk of post-traumatic stress disorder. 61 …”
Section: Discussionmentioning
confidence: 99%
“…Once injected, morphine enters the blood stream, which carries it to the brain and other parts of the body where it acts primarily as an agonist of the μ opioid receptors in the central nervous system and in peripheral tissue. [58][59][60] Recently, Holbrook et al demonstrated that the administration of morphine for optimal control of pain and anxiety after injury may reduce the risk of post-traumatic stress disorder. 61 …”
Section: Discussionmentioning
confidence: 99%
“…However, a longer elimination half-life (2-4 h) and longer context-sensitive half-life (200 min for 6 h infusion and 300 min for 12 h infusion) [19] may be a major shortcoming in long-term sedation as it does not favour rapid NWTs. Fentanyl used as bolus or infusion have again been associated with increased ICP, [42][43][44] and thus it is recommended to be used in patients with stable haemodynamic profile and as stable infusions without significant changes in dosing. [45] Suggested fentanyl doses in patients with traumatic brain injury are 2 mcg/kg test dose followed by 2-5 mcg/kg/h continuous infusion.…”
Section: Need For Additional Drugsmentioning
confidence: 99%
“…[ 4 5 ] Hydrocephalus, chronic opioid use, and bolus dosing of opioid analgesics are also risk factors for disordered breathing during sleep. [ 2 4 5 ] Bolus opiate dosing and sleep apnea associated hypercapnia are known to contribute to intracranial hypertension. [ 2 5 ] Therefore in a patient with clinical evidence of high ICP and chronic opioid use, bolus administrations of opioid analgesics can further increase the ICP.…”
mentioning
confidence: 99%
“…[ 2 4 5 ] Bolus opiate dosing and sleep apnea associated hypercapnia are known to contribute to intracranial hypertension. [ 2 5 ] Therefore in a patient with clinical evidence of high ICP and chronic opioid use, bolus administrations of opioid analgesics can further increase the ICP. [ 2 5 ] Increased ICP can give rise to further downward displacement of the brain into the spinal canal and additional compression of vital brain structures.…”
mentioning
confidence: 99%
See 1 more Smart Citation